2011
DOI: 10.1074/jbc.m110.216382
|View full text |Cite
|
Sign up to set email alerts
|

Acid Ceramidase Expression Modulates the Sensitivity of A375 Melanoma Cells to Dacarbazine

Abstract: Dacarbazine (DTIC) is the treatment of choice for metastatic melanoma, but its response in patients remains very poor. Ceramide has been shown to be a death effector and to play an important role in regulating cancer cell growth upon chemotherapy. Among ceramidases, the enzymes that catabolize ceramide, acid ceramidase (aCDase) has been implicated in cancer progression. Here we show that DTIC elicits a time-and dosedependent decrease of aCDase activity and an increase of intracellular ceramide levels in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 36 publications
5
65
0
Order By: Relevance
“…Notably, whilst DTIC treatment (40 µM) did not induce apoptosis, combined pitavastatin-DTIC treatment resulted in significant levels of apoptosis as evidenced by the increased level of apoptosis markers, cleaved PARP and active caspase 3, as well as annexin V staining. The results of the present study are in agreement with a number of studies which demonstrate that high concentrations of DTIC are necessary to induce apoptosis in melanoma cells (19,32,36). Whilst there has been insufficient research to determine which type of apoptosis is induced by DTIC, sensitization to the intrinsic apoptotic pathway has been revealed to augment DTIC-induced melanoma tumour cell death (37).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Notably, whilst DTIC treatment (40 µM) did not induce apoptosis, combined pitavastatin-DTIC treatment resulted in significant levels of apoptosis as evidenced by the increased level of apoptosis markers, cleaved PARP and active caspase 3, as well as annexin V staining. The results of the present study are in agreement with a number of studies which demonstrate that high concentrations of DTIC are necessary to induce apoptosis in melanoma cells (19,32,36). Whilst there has been insufficient research to determine which type of apoptosis is induced by DTIC, sensitization to the intrinsic apoptotic pathway has been revealed to augment DTIC-induced melanoma tumour cell death (37).…”
Section: Discussionsupporting
confidence: 81%
“…Chemical inhibition of autophagy resulted in enhancement of cell viability, suggesting that pitavastatin-DTIC-induced autophagy occurs as a cell death mechanism. In support of this, previous studies have suggested that DTIC and pitavastatin may serve a function in the induction of autophagy and specifically as a mode of cell death (15,19,38).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…It is metabolized in the liver to an alkylating agent (diazomethane) that destroys cancer cells [8,9], although different mechanism of Dac-toxicity was also suggested [10]. The only available formulation for clinical use is delivered through intravenous injection.…”
Section: Introductionmentioning
confidence: 99%